Microsoft security fundamentals LiveLessons - Lieberman, Ed; Safari eBooks ([Place of publication not identified] : Sams Publishing, 2014)
"In this unique video package, top IT instructor/consultant Ed Liberman helps you master the core skills you need to secure computers and networks, and fully prepare for your MTA 98-367 certification exam. Drawing on his experience helping thousands of people supercharge their IT careers, Ed helps you develop real world skills for success in the fast-growing information security field-and even have fun while you learn. Step by step, you'll learn how to systematically secure computers and networks. Ed covers physical security, authentication, rights/permissions, auditing, encryption, security policies, firewalls, Network Access Protection (NAP), protocol security, Wi-Fi security, malware protection, and more."--Resource description page.
Title from title screen (viewed January 7, 2015).
Presenter, Ed Liberman.
Keywords: Computer security; Computer networks -- Security measures; Electronic books